Diagnosis of bearing defects by variational modes decomposition from vibratory and acoustic emission measurements. (2nd September 2019) - Zarour, Djamal; Thomas, Marc; Meziani, Salim
In order to improve the diagnosis of bearing defects, a new method called variational mode decomposition (VMD) is proposed. This research shows an experimental application for the detection of bearing defects at two stages of degradation: at the early stage and at an advanced stage. In this work, a comparative experimental study between vibratory and acoustic emission measurements, analysed by VMD, is carried out. However, the application of this method requires determining the number of significant frequencies (K) and a balancing parameter (α). For this purpose, the operational modal analysis (OMA) and a correlation study are used to determine the required parameters K and α. The results show that both measurement methods work well to detect the bearing frequencies, but the vibration measurement was more sensitive for an early detection.